Evaluation of burnout among emergency medicine pharmacists. Issue 8 (16th September 2020) - Rozycki, Elizabeth; Bilhimer, Matthew; Bridgeman, Patrick; Slocum, Giles W.; Cocchio, Craig; Weant, Kyle; Groth, Meghan; Sturgill, Marc; Shirk, Mary Beth; Li, Junan; Acquisto, Nicole M.
Abstract: Introduction: Burnout syndrome is a prolonged response to chronic emotional and interpersonal stressors and is becoming an increasing concern in the medical community. Burnout in emergency medicine (EM) pharmacists has not been previously assessed. Objectives: To identify the prevalence of burnout among EM pharmacists, in addition to demographic, professional, seasonal, and job‐related associations. Methods: Pharmacists practicing greater than 50% of their time in the emergency department (ED) setting were invited through the American College of Clinical Pharmacy Emergency Medicine Practice and Research Network listserv to complete a survey at three separate, 4‐week, time periods (July 2018, October 2018, and April 2019). The survey contained the Maslach Burnout Inventory for Medical Personnel to detect burnout. Questions regarding personal and job‐specific demographics were asked. Descriptive statistics were used to report demographics and burnout dimensions in each period. Spearman's rank correlation and univariate and multivariate analyses were performed to identify predictors of burnout and potential associations. Results: A total of 485 surveys were completed across all periods (116 [July], 207 [October], 162 [April]) and response rates were 18.4%, 31.6%, and 22.7%, respectively. Burnout was identified in 69.8%, 67.1%, and 68.5% of respondents with no difference between periods. A majority of participants had high depersonalization scores (50.6‐76.3%) during the three survey periods. Younger age, more ED visits per year, level I trauma center designation, and lower percentage of direct patient care time were associated with increased odds of burnout in the July 2018 period. Intent to leave one's current position or the specialty of EM and consideration of a job with different hours had positive correlations with burnout. Conclusions: Burnout is prevalent in a majority of EM pharmacists throughout the year. It is difficult to identify exact predictors of burnout; however, potential contributors include age, trauma center designation, patient volumes, and direct patient care time.